Relationship Between Oral Health and Demographic Characteristics in Retired Elderly People in Iran - Amir Ahmadi; Robab Sahaf; Vahid Rashedi; Ahmad Ali Akbari Kamrani; Mohsen Shati; Ahmad Delbari (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives The current study aimed to determine the relationship between oral health and demographic characteristics of retired elderly people. Methods & Materials This cross-sectional study was conducted on 158 older adults aged ≥60 years. The subjects were selected using random sampling method and personnel codes. All the elderly participants were retired members of the Tehran Municipality Administration. The study data were collected by direct visit to the subjects' place of residence and conducting interviews. The data collection tool was a questionnaire that included 2 sections. The first section consisted of demographic, socioeconomic, and health profiles, while the second section consisted of Geriatric Oral Health Assessment Index (GOHAI). Results We collected data from 158 participants (90 men, 68 women). The mean age of the participants was 68.78 years. The obtained data suggested that 38 (24.05%) participants had a poor state of oral health. About 50% of the participants mentioned high dental care costs as a reason for not referring to the dentist. According to the findings of this study, there is a direct relationship between educational level and oral health status in the elderly (P<0.05). Conclusion Oral and dental health increase the quality of life in the elderly and reduce the high prevalence of dental problems among them. Therefore, designing and implementing practical policies to reduce oral and dental infections in the elderly and promote their health is necessary.